Classroom Disruptions and Classroom Management in Learning Factory Settings at Vocational Schools - Pierre Meinokat; Ingo Wagner (International Journal for Research in Vocational Education and Training)
Context: As part of vocational education and training, learning factories are a new, hands-on learning setting in which students can create products with realistic digital manufacturing equipment while still in vocational school. Given their novelty, learning factories have not yet been studied with respect to whether special classroom management may be needed. One key aspect of classroom management for teachers is the dealing with classroom disruptions. The aim of this study is to investigate what types of classroom disruptions occur in learning factories and how teachers deal with them.